Effect of Addition of Taurine on the Liquid Storage (5°C) of Mithun (Bos frontalis) Semen - P. Perumal; Kezhavituo Vupru; C. Rajkhowa (Veterinary Medicine International)
The present study was undertaken to assess the effect of taurine on sperm motility, viability, total sperm abnormalities, acrosomal and plasma membrane integrity, enzymatic profiles such as reduced glutathione (GSH), glutathione peroxidase (GPX), superoxide dismutase (SOD), and catalase (CAT), and biochemical profiles such as cholesterol efflux and malondialdehyde (MDA) production. A total of 50 ejaculates were collected twice a week from 8 mithun bulls, and semen was split into 4 equal aliquots and diluted with the TEYC extender. Group 1: semen was without additives (control); groups 2 to 4: semen was diluted with 25 mM, 50 mM, and 100 mM of taurine, respectively. Seminal parameters and enzymatic and biochemical profiles were assessed at 5°C. Inclusion of taurine into diluent resulted in significant () decreases in percentages of dead spermatozoa, abnormal spermatozoa, and acrosomal abnormalities after liquid storage compared with the control group. Additionally, taurine at 50 mM has significant improvement in quality of mithun semen than taurine at 25 or 100 mM stored in in vitro at 5°C. It was concluded that the possible protective effects of taurine on sperm parameters are from enhancing the function of antioxidant enzymes, preventing efflux of cholesterol from cell membranes and decreased MDA production.